Dread disease products : a comparative analysis of actual and expected claims experience in Singapore. - Kuek, Chin Fong. (2013)
Dread Disease Insurance, known also as Living Insurance, Critical Illness or Crisis Cover, is still a relatively new product in Singapore, having been introduced to the Singapore market only in the late 1980s. Relevant dread disease incidence data are therefore currently unavailable, and insurers have to resort to estimating dread disease incidence rates when pricing the product. As insurance companies may suffer adversely if the rates are inadequate, insurers need to ensure that these estimated rates are sufficient to cover the probable claims. This report provides an examination of the various methods used by the insurers in estimating dread disease incidence rates, namely age rating and percentage rating on standard tables and reinsurance rates. Expected incidence rates are obtained from these estimation methods and compared with actual dread disease incidence rates derived from data collected from insurers in Singapore. For reasons of confidentiality, the data collected are not included in this report. Finally, optimal age and percentage rate-ups (or downs) on the standard tables and reinsurance rates are proposed.